The Association Between Vulnerable/Grandiose Narcissism and Emotion Regulation - Loeffler, Leonie A. K.; Huebben, Anna K.; Radke, Sina; Habel, Ute; Derntl, Birgit (Frontiers in Psychology, 2020)
Narcissism has been widely discussed in the context of career success and leadership. Besides several adaptive traits, narcissism has been characterized by difficulties in emotion regulation. However, despite its essential role in mental health, there is little research on emotion regulation processes in narcissism. Specifically, the investigation of not only the habitual use of specific regulation strategies but also the actual ability to regulate is needed due to diverging implications for treatment approaches. Thereby it is important to differentiate between vulnerable and grandiose narcissism as these two phenotypes might be related differently to regulation deficits. The aim of this study was to examine the association between grandiose and vulnerable narcissism and emotion regulation in healthy individuals (30f/30m) focusing on the strategy reappraisal. Additionally, potential sex effects have been explored. Narcissism was assessed using self-report measures and emotion regulation with self-report questionnaires as well as an experimental regulation task. During this task, participants were presented with pictures of sad/happy faces with the instruction to indicate their subjective emotions via button press. Depending on the condition, participants either indicated their natural response or applied cognitive control strategies to regulate their own subjective emotions. Results indicate no relationship between grandiose and vulnerable narcissism and emotion regulation ability, irrespective of sex. Individuals high on vulnerable narcissism use the maladaptive regulation strategy suppression more frequently than individuals with low expressions. Individuals high on grandiose narcissism, in contrast, seem to avoid the suppression of positive emotions and do not express negative emotions in an uncontrolled manner. Interestingly, while grandiose narcissism was not associated with depressive symptoms, vulnerable narcissism correlated positively with depressive symptoms and anhedonia. Findings of this study underline the need to differentiate between grandiose and vulnerable manifestations of narcissism. Against our expectation, narcissism was not related to emotion regulation performance. In line with previous research, grandiose narcissism seems less harmful for mental health, while vulnerable narcissism is associated with psychological problems and the use of rather maladaptive emotion regulation strategies, i.e. suppression. Future research should investigate the relationship between pathological narcissism and emotion regulation also by extending the scope to other relevant regulation strategies.